Management of Pregnancy in Women of Advanced Maternal Age: Improving Outcomes for Mother and Baby - Glick I; Kadish E; Rottenstreich M (Dove Medical Press, 2021)
Itamar Glick,1 Ela Kadish,2 Misgav Rottenstreich1,3 1Department of Obstetrics & Gynecology, Shaare Zedek Medical Center and Faculty of Medicine, Hebrew University of Jerusalem, Jerusalem, Israel; 2Faculty of Medicine, Hebrew University of Jerusalem, Jerusalem, Israel; 3Department of Nursing, Jerusalem College of Technology, Jerusalem, IsraelCorrespondence: Misgav RottenstreichDepartment of Obstetrics and Gynecology, 12 Bayit Shaare Zedek Medical Center, Jerusalem, 91031, IsraelTel +972 2- 655-5562Fax +972 2- 666-6053Email misgavr@gmail.comAbstract: Pregnancy at advanced maternal age (age > 35 years old) is considered a risk factor for adverse maternal and perinatal outcomes. Yet, pregnancies of advanced maternal age have become more prevalent over the last few decades. Possible maternal complications of pregnancy at age 35 or older include increased risk of spontaneous miscarriage, preterm labor, gestational diabetes mellitus, pre-eclampsia, stillbirth, chromosomal abnormalities, and cesarean delivery. Possible adverse fetal outcomes include infants small for gestational age and intrauterine growth restrictions, low Apgar score, admission to neonatal intensive care units, and an autism spectrum disorder. This paper aims to present an up-to-date review of the literature, summarizing the most current studies and implications for the management of pregnancy of advanced maternal age.Keywords: advanced maternal age, adverse maternal outcome, adverse perinatal outcome